Determinan Kredit Bank Umum untuk Sektor Pertanian: Analisis dari Sisi Permintaan dan Penawaran - Yunnise Putri; Idris Idris (Universitas Negeri Padang, 2020)
This study examines Agricultural Loans Determinants: Analysis from the Supply and Demand Side with the scope of Indonesia starting from 2012 to 2019. This study uses Error Correction Model (ECM) analysis as an estimation method that shows the effect of the independent variable on the dependent variable in the short term. as well as long term. The results of the study show that in the short term, the variables of CAR, NPL and Inflation have a negative effect on Commercial Bank Loans for the Agricultural Sector, while the variables of TPF, Economic Activity and Loan Interest Rates have a positive effect. On the other hand, in the long term, the variables of DPK, Economic Activity and Loan Interest Rates actually have a negative effect and it is the variables of CAR, NPL and Inflation that have a positive effect on Commercial Bank Loans for the Agricultural Sector.